PERANAN GIBBCRELLINT TERRHADAP PERKECAMBAHAN BENIH KOPI ROBUSTA (COFFEA CANEPHORA PIERRE) TANPA KULIT - Murniati '; Elza Zuhry (Universitas Riau, 2002)
Coffee seed has endocurp that is inipcrnicabic who water and Oj, because it contains com-plex of polysaccharide, hemicellulosc, fat and protein. This condition could prevent germi-nation. To overcome this problem, there are several alternatives available, one of them bypeeling endocarp and submerging in gibberellin hormone solvent. This experiment wasconducted in Breeding Laboratory, College of Agriculture, University of Riau. The designM a s Complete Randomized Varianged in factorial 2 factors. First factor is three levels ofgibberellin (0 ppm, 10 ppm and 20 ppni) and the second factor is 3 endocarp treatments(without peeling, 50 % of peeUng and 100 % of peeling). The results showed that 100 %peeling and submerging in gibberellin of 20 ppm could accelerate and increase germinationpercentage, howives cotyledon breaker, there is no significant difference among the inter-action of giberalin and peeling endocarp.